Confronting Energy Poverty in Europe: A Research and Policy Agenda - Stefan Bouzarovski; Harriet Thomson; Marine Cornelis (Energies, 2021)
This paper scrutinizes existing policy efforts to address energy poverty at the governance scale of the European Union (EU) and its constituent Member States. Our main starting point is the recent expansion of energy poverty policies at the EU level, fuelled by the regulatory provisions of the Clean Energy for all Europeans Package, as well as the establishment of an EU Energy Poverty Observatory. Aided by a systematic and customized methodology, we survey the extensive scientific body of work that has recently been published on the topic, as well as the multiple strategies and measures to address energy poverty that have been formulated across the EU. This includes the principal mitigation approaches adopted by key European and national institutions. We develop a framework to judge the distributional and procedural justice provisions within the recently adopted National Energy and Climate Plans, as an indicator of the power, ability and resolve of relevant institutions to combat the causes and consequences of energy injustice. We also provide a research and policy agenda for future action, highlighting a series of scientific and decision-making challenges in the European and global context.